Methamphetamine/amphetamine use over time among persons with opioid use disorders treated with buprenorphine/naloxone versus extended-release naltrexone. (1st July 2022) - Tsui, Judith I.; Campbell, Aimee N.C.; Pavlicova, Martina; Choo, Tse-Hwei; Lee, Joshua D.; Cook, Ryan R.; Shulman, Matisyahu; Nunes, Edward V.; Rotrosen, John
Abstract: Background: Methamphetamine use is increasing among persons with opioid use disorder (OUD). The study aims were to describe methamphetamine/amphetamine (MA/A) use among patients treated for OUD with buprenorphine/naloxone (BUP-NX) or extended-release naltrexone (XR-NTX), and to explore associations between treatment arm and MA/A use. Methods: Secondary analysis of data from a multi-site, open-label, randomized controlled trial of XR-NTX versus BUP-NX for 24 weeks. The outcome variable was MA/A use defined by either positive urine drug toxicology or self-report. The main predictor was treatment assignment (BUP-NX v. XR-NTX). Longitudinal mixed-effects logistic regression models were fit to model the odds of MA/A use during the study. Additional predictors included study visit and baseline MA/A use. Results: Among the sample of 570 participants with OUD, baseline use of MA/A was observed in 105 (18.4%). There was no significant treatment effect over the study period, though BUP-NX subjects, on average, had about half the odds of MA/A use compared to XR-NTX subjects (OR=0.50; p = 0.051). In the same model, baseline MA/A use and study visit were both significantly associated with MA/A use over time. Conclusion: In this sample of treated OUD patients, nearly a fifth of participants had MA/A use at baseline and the frequency of use did not decline over time: in fact, the odds of use slightly increased for each later visit. These secondary analyses found no significant difference in MA/A use between BUP-NX and XR-NTX treatment arms, however, the observation of less MA/A in the buprenorphine arm merits further investigation. Clinical trial registration: ClinicalTrials.gov (NCT02032433) Highlights: Among patients with treated opioid use disorder, nearly a fifth used methamphetamine/amphetamine (MA/A) baseline. Baseline use predicted future use, and MA/A use slightly increased at later visits. This secondary analysis found no significant difference, however, the observation of less MA/A use in the BUP-NX v. XR-NTX arm (OR=0.50; p=0.51) merits further investigation.